DOCKING STUDIES ON ANTICANCER EFFECT OF MENTHA PIPERITA AND OCIMUMBASILICUM AGAINST BREAST CANCER - S. K. GANGAI ABIRAMI; Dr.P.NIRMALA (International Journal of Pharma and Bio Sciences, 2014)
Cancer research is the intense scientific effort to understand disease processes and discover possible therapies. Breast cancer is the second most common type of cancer after lung cancer. Normal breast cells and most breast cancer cells have receptors that attach to circulating estrogen and progesterone. In the present study, cha-rasprotein and cytochrome P450 was docked with the two drugs and the energy value obtained for limonene (-6.07762 kcal/mol) with elapsing time of 5 seconds, Eugenol (-6.53482 kcal/mol) with elapsing time of 7 seconds, using Argus lab docking software.